TACKLING THE PAINS OF CORONAVIRUS LOCKDOWN THROUGH PALLIATIVES IN NIGERIA: ADDRESSING THE GAPS AND CRITICAL STRATEGIC ISSUES - N. ONAH, Ph.D, FRANCISCA; O. UGWUIBE, Ph.D, CHRISTOPHER; O. ONAH Ph.D, FAB. (International Journal of Psychosocial Rehabilitation, 2021)
On March 11, 2020 the World Health Organization (WHO) upgraded the status of the novel coronavirus, also known as COVID-19 outbreak, from epidemic to pandemic. Ever since then, the world has been reeling from the catastrophic spread of the virus. Consequently, Nigeria rolled out a couple of measures to reduce the spread of the virus in the country in keeping with WHO guides. In addition, the Federal Government and most States in the Federation declared lockdown in the state and closure of states and national borders. The study investigated the effectiveness and interrogated the template used in distributing the palliatives to the poor. The results showed that the templates used in the distribution of the palliatives were highly ineffective and that inadequate data base and politics negatively impacted on the implementation of the palliatives meant for the poor. The study recommended among others that for strategic reasons ,sufficient and disaggregated data should be generated, updated, and stored for future use in Nigeria for the purpose of bringing the warmth of governance to all who are in need